Improving Physical Health Monitoring on a Working-Age General Adult Inpatient Ward: A Quality Improvement Project - Mohsin Nazeer Muhammed; Abeer Jawed; Nadarasar Yoganathan (BJPsych Open)
Aims: Individuals with severe mental illness (SMI) face a significantly reduced life expectancy, primarily due to preventable physical health conditions. This project aimed to enhance the timeliness and comprehensiveness of physical health checks for inpatients in an acute psychiatric ward. An initial audit cycle identified gaps, prompting targeted interventions, with subsequent re-audit assessing their impact.